The Implementation of Contextual Teaching and Learning (CTL) to Foster Students’ Social Attitudes in Social Studies Learning at SMPN 1 Gedangan - Dwi Jayanti, Annisa Fithri; Afifah, Silvi Nur; Larasati, Dian Ayu; Virgiawan, Dhimas Bagus (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the implementation of Contextual Teaching and Learning (CTL) in forming students’ social attitudes in Social Studies learning at SMPN 1 Gedangan. This research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with Social Studies teachers and students, and documentation of learning activities. The research focused on Social Studies learning with the theme of Indonesian Societal Diversity, which was implemented based on the Merdeka Curriculum using teaching modules as the main instructional reference. The findings indicate that the implementation of CTL played an important role in developing students’ social attitudes, including cooperation, responsibility, tolerance, empathy, and self-confidence. These attitudes emerged through learning activities that emphasized real-life contexts, group discussions, collaborative problem-solving, and reflective learning. Students actively participated in learning processes that encouraged interaction and the exchange of ideas, enabling them to internalize social values through meaningful experiences. The formation of students’ social attitudes was influenced by the quality of social interaction, teacher facilitation, and a supportive classroom environment. Learning activities connected to students’ daily lives allowed them to better understand social values and apply them in everyday interactions. The study concludes that Contextual Teaching and Learning is an effective pedagogical approach for integrating academic learning with the development of social attitudes through authentic and interaction-based learning experiences in Social Studies education.